Stylish stores vol 1 - Lee, Ying (Hong Kong, 2017)
"Stores have constantly strengthened the concept 'brand' in the process of their emergence and development. Hence the design has become more and more unique. The book, as a continuation of the style in Stylish Store Design I, brings together the latest design of international fashion stores all over the world, reflecting the trend of modern international fashion store design, among which many well-known design companies are included. It is worthy of reading and reference"--Provided by publisher
Keywords: Store decoration; Display of merchandise; Illustrated works -- Retail Design and construction